Assessment of plasma cell myeloma minimal residual disease testing by flow cytometry in an international inter‐laboratory study: Is it ready for primetime use?. Issue 3 (19th December 2018) - Scott, Stuart D.; Fletcher, Matthew; Whitehouse, Helen; Whitby, Liam; Yuan, Constance; Mazzucchelli, Silvia; Lin, Pei; de Tute, Ruth; Dorwal, Pranav; Wallace, Paul K.; Tembhare, Prashant; Arroz, Maria; et al.
Abstract : Background: Minimal/measurable residual disease (MRD) testing by flow cytometry (FC) has been proposed as a potential surrogate clinical endpoint in plasma cell myeloma (PCM) clinical trials. As a result, effort has gone into standardizing this approach on PCM patients. Aims: To assess inter‐laboratory variation in FC MRD testing of PCM patients in an independent inter‐laboratory study. Methods: A dilution series of five stabilized bone marrow samples manufactured to contain 0%, 0.1%, 0.01%, 0.001%, and 0.0001% neoplastic plasma cells (PCs) were tested blind, using standardized FC PCM MRD assays by 10 international laboratories. Results: Laboratories' assays broadly adhered to the consensus guidelines; however, some deviations were identified in panel design, fluorochrome conjugates, and lysis reagents. Despite this, all laboratories that returned results detected neoplastic PCs down to 0.001% of leucocytes. 6/8 laboratories detected neoplastic PCs at a level of 0.0001%. Quantitative data returned by laboratories showed good consensus and linearity with increasing variation at lower levels of MRD. However, examples of analytical and post analytical error were identified. Summary/Conclusion: Broadly standardized PCM MRD FC assays can attain the lower limit of detection (LOD) required by current and future clinical trials, an important consideration in establishing PCM MRD testing as a surrogate clinical marker in PCM clinical trials. Laboratories' assays showed good linearity, encouraging the prediction of survival based on log reduction in neoplastic PC populations in future clinical trials. However, the deviations from consensus guidelines identified in this study would suggest that if PCM MRD assays are further standardized interlaboratory variation could be reduced. © 2018 International Clinical Cytometry Society